Low interest rate regime and the transmission of monetary policy through the lending channel in Malaysia: evidence from bank-level data - Asbeig, Hussam I.; Kassim, Salina (2013)
Monetary policy in Malaysia has been designed to be accommodative and supportive of economic growth with balancing the risk of inflation. As the cost of borrowing remains low, the transmission of monetary policy through the traditional interest rate channel might be diminished. Moreover, the influential presence of the Islamic banks has further compounded the transmission process of monetary policy via interest rate channel. This study investigates the impact of monetary policy actions on the supply of loan/financing based on bank specific characteristics namely, size, liquidity and capitalization. The study adopts a multiplicative model based on panel data approach. We utilise balanced annual panel data that covers the period from 2000 to 2011. The study finds that bank specific factors, specifically, size and liquidity play an important role for the lending behaviour of the Islamic and conventional banks, whereas capitalization is significant only for the Islamic banks. Additionally, the study finds that the annual changes in the monetary policy have no significant impact on the level of financings of both the Islamic and conventional banks in Malaysia. We also find that monetary policy has no distributional effect on bank financings across capitalization, liquidity, size, and type during the study period, which does not help identify the financing/lending channel in Malaysia.